Longitudinal relations between beliefs supporting aggression and externalizing outcomes: Indirect effects of anger dysregulation and callous‐unemotional traits. Issue 1 (26th October 2018) - Hitti, Stephanie A.; Sullivan, Terri N.; McDonald, Shelby E.; Farrell, Albert D.
Abstract : Aggression is prevalent in early‐ to mid‐adolescence and is associated with physical health and psychosocial adjustment difficulties. This underscores the need to identify risk processes that lead to externalizing outcomes. This study examined the extent to which the effects of three dimensions of beliefs supporting aggression on physical aggression and externalizing behavior are mediated by anger dysregulation and callous‐unemotional (CU) traits. Three waves of data were collected from a primarily African American (77%) sample of 265 middle school students between the ages of 11 and 15 (52% were female). We found evidence supporting mediation such that the effects of beliefs supporting instrumental aggression and beliefs that fighting is sometimes necessary at Wave 1 on student‐reported physical aggression at Wave 3 were mediated by CU traits at Wave 2, and relations between beliefs supporting reactive aggression at Wave 1 and teacher‐report of student frequencies of physical aggression and externalizing behavior at Wave 3 were mediated by anger dysregulation at Wave 2. Our findings demonstrated the importance of distinguishing between dimensions of beliefs supporting aggression, as differential paths emerged between specific beliefs, CU traits and anger dysregulation, and externalizing outcomes. These findings have important clinical implications, as they suggest that specific dimensions of beliefs supporting aggression could be targeted based on whether an individual is at risk for behavior patterns characterizing CU traits or anger dysregulation.